Takana loistava tulevaisuus - suomalaisen terveydenhuollon tietoteknologian neljä ensimmäistä vuosikymmentä - Mikko Nenonen (Finnish Social and Health Informatics Association, 2012)
In 70's and at the beginning of 80's Finland was one of the most advanced countries in introducing information systems into healthcare. The first system in primary health care was Finstar, a localized version of Costar. Soon the field was, however, left to software business which introduced more primitive health information systems copying the paper journal into computer systems without any value added services. These programs created less change resistance and thus conquered the market. Now after nearly 40 years these first to second generation programs are the biggest problem of Finnish healthcare preventing development, compromising patient safety and consuming about 10 % of the health personnel resources. Moving into modern health information systems would demand an investment of 3 to 5 billion Euros (3 000 to 5 000 million Euros).